1993
DOI: 10.1136/oem.50.7.642
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and occupation: results of a case-control study in The Netherlands.

Abstract: Incidence of cutaneous melanoma has been increasing rapidly in the past decades and a doubling of incidence every decade has been found.' Exposure to sunlight is considered to be the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Similarly, studies of chemical workers have also shown elevated risks of melanoma [171,179,224]. Cohort studies of electrical and electronics workers [146,203,220] along with at least one case-control study [179] have also shown elevated risks for melanoma. It has been hypothesized that workers in occupations exposed to ionizing radiation might also be at increased risk of melanoma [3,71,218,238,252].…”
Section: Occupation and Melanomamentioning
confidence: 97%
“…Similarly, studies of chemical workers have also shown elevated risks of melanoma [171,179,224]. Cohort studies of electrical and electronics workers [146,203,220] along with at least one case-control study [179] have also shown elevated risks for melanoma. It has been hypothesized that workers in occupations exposed to ionizing radiation might also be at increased risk of melanoma [3,71,218,238,252].…”
Section: Occupation and Melanomamentioning
confidence: 97%
“…Many non-UV-related factors have been proposed as contributing to the risk of melanoma, but no coherent etiologic picture has emerged (10,11). Most notably and relevant to our proposal is that many epidemiological studies have shown an increased risk of melanoma in many occupations associated with the electronic and chemical industries (12)(13)(14)(15)(16). We propose that the attributable risk not explained by UV light exposure or genetic risk can largely be understood by using a model that proposes that increases in reactive oxygen species are central to the pathogenesis of melanocyte transformation and melanoma progression (Fig.…”
mentioning
confidence: 99%
“…Recently, overexpression of one of these enzymes has been associated with a poor prognosis in patients with melanoma (39). Nonmetals of particular interest that also bind melanin would include organic amines, polychlorinated biphenyls, pesticides, herbicides, and dyes (12)(13)(14)(15)(16), and further study of risk for melanoma using agricultural health data bases might be informative. Advances in occupational epidemiology and the ability to measure metals at low concentrations in individual cells in tissue (e.g., inductively coupled plasma spectrometry, inductively coupled plasma-mass spectrometer; Refs.…”
mentioning
confidence: 99%
“…Although exposure to sunlight is considered to be the most important environmental risk factor, increased risks of cutaneous melanomas were found for workers who were exposed to various chemicals in the electronics and metal industries and transport and communication branch (21). The Fischer-344 (F-344) rat is a common strain of rodents used in carcinogenicity studies, but very little is known concerning the occurrence of their cutaneous amelanotic melanomas.…”
Section: Introductionmentioning
confidence: 99%